Interfacial-active polymer nanoparticles, their assemblies, and SERS application - Visaveliya, Nikunjkumar R.; Li, Xiang; Knauer, Andrea; Prasad, Bhagavatula L. V.; Kohler, Johann Michael (Macromolecular Chemistry and Physics, 2017)
In this work, surface-active polymer nanoparticles as well as polymer-polymer and polymer-metal nanoassembly particles are synthesized, and different parameters such as their size, morphologies, and assembling strength are studied. Nanoassembly particles are attractive because of the coupled properties with a large surface to volume ratio. A key challenge is to produce the core-shell polymer nanoparticles via single-step processes. To address this concern, here, microfluidics approach and precise interfacial reaction strategies are used, and hence different types of surface layered polymer nanoparticles are obtained in one-step processes. An inner core material is hydrophobic, whereas a hydrophilic surface layer (in situ formed during the polymerization process) swells in the aqueous environment. Moreover, three different reaction setups (batch, flow, and in situ) are applied in order to architect the nanoassembling hierarchical structures via layer-by-layer strategy. On the other side, polymer-metal nanoassembly particles as well as metal catalyzed metal deposited four layered nanoassembly particles of tuned size and compositions are produced. It is shown that these particles can be used as nanosensor particles for surface-enhanced Raman spectroscopy.

Influence of van der waals interactions between the alkyl chains of surface ligands on the size and size distribution of nanocrystals prepared by the digestive ripening process - Shimpi, Jayesh R.; Thomas, Rinto; Meena, Santosh Kumar; Prasad, Bhagavatula L. V. (Langmuir, 2023)
Thermal heating of polydispersed nanocrystals (NCs) with surface-active organic ligands in a solvent leads to the formation of monodispersed NCs, and this process is known as digestive ripening (DR). Here, by performing DR on Au NCs using different-chain-length amine and thiol ligands, we evidently show that ligands with C-12 chain length result in the formation of NCs with narrow size distributions when compared to C-8, C-16, and C-20 chain length ligands. Furthermore, our findings also show that in the case of alkyl thiol, the NC size remains more or less the same, while the size distribution gets altered significantly with the chain length. On the other hand, both size and size distribution are affected significantly when the alkyl amine chain length is varied. Fourier transform infrared (FTIR) studies indicate that the van der Waals (vdW) interactions are weakest when the amine with C-12 carbon chain is used as the DR agent, while in the case of thiols, molecules with C-8 and C-12 chain lengths have nearly the same vdW interactions (with C-12 slightly weaker than C-8), which are weaker than those of C-16 and C-20. Molecular dynamics (MD) simulation results corroborate the experimental observations and suggest that due to more defects in the alkyl chain, the C-8 and C-12 (amine as well as thiol) ligands are disordered and less stable on Au(111) and Au(100) surfaces. This could result in efficient etching and redeposition, making the ligands with C-8 and C-12 chain lengths the better DR agents.